PERPADUAN NILAI DAKWAH DAN ESTETIKA DALAM NOVEL KAMBING DAN HUJAN KARYA MAHFUD IKHWAN - Naufal, Mazka Hauzan (Islamic Communication Journal, 2018)
The growth of islamic literature keeps a problem. For some critics, many works of fiction labeled